Host–Guest Complexation‐Induced Aggregation Based on Pyrene‐Modified Cyclodextrins for Improved Electronic Circular Dichroism and Circularly Polarized Luminescence. (18th May 2022) - Tu, Chenlin; Wu, Wanhua; Liang, Wenting; Zhang, Dongjing; Xu, Wei; Wan, Shigang; Lu, Wei; Yang, Cheng
Abstract: Several γ‐cyclodextrin (CD) derivatives mono‐ or di‐substituted by pyrenes at the primary rim of the CD were demonstrated to aggregate into nano‐strips in aqueous solutions, with the pyrene moieties interpenetrating into γ‐CD cavities. The hydrophobic complexation‐induced aggregation provides a rigid chiral environment for the pyrenes and leads to significant electronic circular dichroism (ECD) and circularly polarized luminescence (CPL) activities, giving unprecedently high g abs and g lum values up to 4.3×10 −2 and 5.3×10 −2, respectively. The aggregates lead to excimer emission with high quantum yields and show B CPL and B i CPL up to 338. 6 M −1  cm −1 and 169.3 M −1  cm −1, respectively. Abstract : The self‐assembly of di‐pyrene‐substituted γ‐CD in water showed significantly high chiroptical activities and gave g abs and g lum values up to 4.3×10 −2 and 5.3×10 −2, respectively. Meanwhile, it provided remarkable chiral emission performance, with the B CPL and B i CPL values reaching 338.6 M −1  cm −1 and 169.3 M −1  cm −1, respectively.